Investigations of the unsteady aerodynamic characteristics for intakes at crosswind - Piovesan, Tommaso; Wenqiang, Zhang; Vahdati, Mehdi; Zachos, Pavlos K. (American Society of Mechanical Engineers (ASME), 2022)
The ground vortex generated in front of an intake operating near the ground and subjected to crosswind is investigated using CFD and compared to the experiments. The flow field of a scale-model intake is numerically simulated with both steady and unsteady approach, with the aim of predicting ground vortex effects and to characterize the vortex unsteady behaviour. The experimental results showed that for an intake near the ground under crosswind the ground vortex that forms under the intake and the in-duct separation, when present, exhibit unsteady behaviour that becomes stronger as the crosswind velocity is increased. The simulations indicate that a steady-state approach only partially reproduces the time-averaged ground vortex characteristics and in-duct distortion losses, while an unsteady approach shows a lower level of unsteadiness compared to the experimental observations. The consequences of the unsteady flow in the intake on the fan aerodynamic and aeroelastic stability are finally discussed to reinforce that these can result in significant non-synchronous vibration (NSV) and loss of stall margin which cannot be adequately assessed if no unsteady component of the inlet distortions is taken into account.